Studies on the restriction of murine leukemia viruses by mouse APOBEC3. - Silvia Sanchez-Martinez; Amanda L Aloia; Demetria Harvin; Jane Mirro; Robert J Gorelick; Patric Jern; John M Coffin; Alan Rein (PLoS ONE)
APOBEC3 proteins function to restrict the replication of retroviruses. One mechanism of this restriction is deamination of cytidines to uridines in (-) strand DNA, resulting in hypermutation of guanosines to adenosines in viral (+) strands. However, Moloney murine leukemia virus (MoMLV) is partially resistant to restriction by mouse APOBEC3 (mA3) and virtually completely resistant to mA3-induced hypermutation. In contrast, the sequences of MLV genomes that are in mouse DNA suggest that they were susceptible to mA3-induced deamination when they infected the mouse germline. We tested the possibility that sensitivity to mA3 restriction and to deamination resides in the viral gag gene. We generated a chimeric MLV in which the gag gene was from an endogenous MLV in the mouse germline, while the remainder of the viral genome was from MoMLV. This chimera was fully infectious but its response to mA3 was indistinguishable from that of MoMLV. Thus, the Gag protein does not seem to control the sensitivity of MLVs to mA3. We also found that MLVs inactivated by mA3 do not synthesize viral DNA upon infection; thus mA3 restriction of MLV occurs before or at reverse transcription. In contrast, HIV-1 restricted by mA3 and MLVs restricted by human APOBEC3G do synthesize DNA; these DNAs exhibit APOBEC3-induced hypermutation.